Rancang Bangun Wireless Signage Menggunakan Mikroprosesor Raspberry Pi - Nisa, Khairun; Anwar, Anwar; Nasir, Muhammad (eProceeding of TIK, 2022)
Digital Signage is a form of conveying information through electronic (dynamic) display media. So far, academic information and other announcements are still displayed conventionally or in the form of papers and leaflets. The existence of LCD screens, TV monitors and wireless has not been implemented optimally so that it seems less effective. Therefore, with this Wireless Digital Signage, it is hoped that academic information and other announcements can be displayed digitally, accurately, quickly and attractively. This research uses descriptive qualitative research method, where the type of descriptive research used is Design and Creation, which is a type of research to develop products in the field of technology and information. While the data collection method used is literature study method. The analysis carried out is system analysis and application analysis. Digital signage is tested using each block test, which is testing each hardware function, received data format, and software testing in terms of functional specifications. Testing is intended whether the input and output functions of the device are in accordance with the required specifications. The test results obtained are that many formats are accepted, starting from images and videos, as well as the results of the process of use and testing carried out with a delay or interval of data from the upload process to the display process which is only less than 2 minutes, which shows that the system is very responsive to its use. In this study, the QoS (Quality of Service) method is also used to measure the delay caused on the network used. The test results were late as many as 25 times in the study, the delay resulted in 0.1393 seconds.